2015
DOI: 10.4103/0971-4065.145097
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of urinary liver-type fatty acid binding protein at various stages of nephropathy

Abstract: This cross-sectional study was to evaluate the levels of urinary liver-type fatty acid binding protein (u-LFABP pg/mg urine creatinine ratio) at different stages of diabetic nephropathy and to see its correlation with other clinical parameters in South Indian patients with type 2 diabetes mellitus (T2DM). A total of 65 (M: F; 42:23) T2DM subjects were divided into three groups, and were compared with 13 (M: F; 3:10) nondiabetic controls. The study groups were as follows: normoalbuminuric (n = 22), microalbumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 17 publications
1
18
1
2
Order By: Relevance
“…Urinary L-FABP levels were significantly increased in macroalbuminuric patients compared with microalbuminuric and currently normoalbuminuric patients [ 46 ]. In one study from type 2 diabetes mellitus patients, elevated levels of urinary L-FABP were evident from the microalbuminuric stage, indicating tubular damage at the early stage of DN [ 50 ]. According to this study, urinary excretion of L-FABP levels in the microalbuminuric group was significantly correlated with systolic BP, fasting plasma glucose, and HbA1c, which indicated that urinary L-FABP could be most sensitive marker for detecting glomerular and tubular dysfunction at the early stage of DN [ 50 ].…”
Section: Liver-type Fatty Acid Binding Proteinmentioning
confidence: 99%
“…Urinary L-FABP levels were significantly increased in macroalbuminuric patients compared with microalbuminuric and currently normoalbuminuric patients [ 46 ]. In one study from type 2 diabetes mellitus patients, elevated levels of urinary L-FABP were evident from the microalbuminuric stage, indicating tubular damage at the early stage of DN [ 50 ]. According to this study, urinary excretion of L-FABP levels in the microalbuminuric group was significantly correlated with systolic BP, fasting plasma glucose, and HbA1c, which indicated that urinary L-FABP could be most sensitive marker for detecting glomerular and tubular dysfunction at the early stage of DN [ 50 ].…”
Section: Liver-type Fatty Acid Binding Proteinmentioning
confidence: 99%
“…Several studies on adult patients with diabetes have consistently supported that L-FABP is an early marker for tubular injury which is in agreement with the current study. Viswanathan et al [24] and Panduru et al [25] found that L-FABP was an independent predictor of progression of DN. Kamijo-Ikemori et al [26] and Nielsen et al [13] concluded that high levels of urinary L-FABP could predict DN.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of tubular damage in the early stages of diabetic nephropathy has been reported in various studies done on urinary biomarkers in diabetic patients. [12][13][14][15][16] In our study we tested urinary periostin as a biomarker to diagnose renal injury in type 2 diabetic subjects. Periostin expression in kidney and its detection in urine during renal injury has been demonstrated in very few studies.…”
Section: Discussionmentioning
confidence: 99%